Differential effects of glucocorticoids in the establishment and maintenance of endotoxin tolerance - Rearte, María Bárbara (2010)
Gram-negative infections can result in endotoxic shock, which is the most common cause of death in intensive care units. Most of the undesirable effects in sepsis and septic shock have been ascribed to lipopolysaccharide (LPS), a normal constituent of the bacterial wall. The response to LPS involves rapid secretion of proinflammatory cytokines [tumour necrosis factor-α, interleukin (IL)-1, IL-6, IL-8, interferon-γ] and the concomitant induction of anti-inflammatory mediators such as IL-10 and transforming growth factor-β and glucocorticoids (GC), which render the host temporarily refractory to subsequent lethal doses of LPS challenge in a process known as LPS or endotoxin tolerance. Although protective from the development of sepsis or systemic inflammation, endotoxin tolerance has also been pointed out as the principal cause of the non-specific immunosuppression described in these patients. In this report we demonstrate, using a mouse model, that while the maintenance of tolerance is dependent upon GC, the establishment of tolerance by LPS could be inhibited by dexamethasone (Dex), a synthetic GC. Conversely, we demonstrated that mifepristone (RU486), a known GC receptor antagonist, was capable of inducing a transient and reversible disruption of endotoxin tolerance, also permitting partial restoration of the humoral immune response in LPS tolerant/immunosuppressed mice. These results are encouraging for the management of immunosuppression in sepsis and/or non-infectious shock, and deserve further investigation in the future. © 2009 British Society for Immunology.